2021
DOI: 10.1111/ejn.15136
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology linking depression and type 2 diabetes: Psychotherapy, physical exercise, and fecal microbiome transplantation as damage control

Abstract: Diabetes increases the likelihood of developing depression and vice versa. Research on this bidirectional association has somewhat managed to delineate the interplay among implicated physiological processes. Still, further exploration is required in this context. This review addresses the comorbidity by investigating suspected common pathophysiological mechanisms. One such factor is psychological stress which disturbs the hypothalamic–pituitary–adrenal axis causing hormonal imbalance. This includes elevated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 330 publications
(313 reference statements)
3
24
0
13
Order By: Relevance
“…According to our multidimensional analysis, Alistipes can be a potential biomarker of the development of T2D. Still, further studies will be necessary in the near future to better de ne the role of this genus when T2D is accompanied by other comorbidities [73]. For instance, it has been reported that T2D patients have higher levels of depression incidence [74].…”
Section: Discussionmentioning
confidence: 93%
“…According to our multidimensional analysis, Alistipes can be a potential biomarker of the development of T2D. Still, further studies will be necessary in the near future to better de ne the role of this genus when T2D is accompanied by other comorbidities [73]. For instance, it has been reported that T2D patients have higher levels of depression incidence [74].…”
Section: Discussionmentioning
confidence: 93%
“…Thereby, a link between obesity and MDD was reported [ 36 ]. Moreover, RETN is involved in the interrelationship between MDD and diabetes, whereby neuroinflammation was reported to be of certain relevance [ 37 ]. This is a potential and interesting connecting point of MDD and PD; RETN was found to be elevated in gingival crevicular fluid and serum of patients with PD, although this was not related to systemic inflammatory diseases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with senile dementia, the brainstem had poor regulation of respiratory function, and the lungs had a greatly diminished ability to clear pathogens, which, combined with the fact that they often present with language impairment and had difficulty expressing subjective sensation, thereby delaying the treatment [ 34 ]. Studies have shown that multiple neuroendocrine hormone abnormalities are present in patients with diabetes mellitus, manifested by glucocorticoid hypersecretion and dysfunction of hypothalamo-hypophyseal-thyroidal axis (HHTA) [ 35 37 ]. Moreover, with increasing age, HHTA also becomes progressively aged, leading to hypothyroidism manifested by reduced respiration, hypothermia, and hyporeflexia, which can mask infectious symptoms and lead to occult pulmonary infections [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%